Kebaya dan Kelas Sosial Wanita Jawa pada Masa Kolonial (1890-1940): Perspektif Habitus Bourdieu - Azzahra, Nadya Salma; Sakinah, Adiyba Humaira; Ulya, Syafaatul (Socio Historica: Journal of Islamic Social History, 2023)
This research aims to find out the relationship between kebaya and social class of Javanese women during the colonial period (1890-1940) by using the perspective of Pierre Bourdieu's habitus theory, as well as knowing how kebaya plays a role in emphasising the social structure during the colonial period. The method used is the historical method with literature study analysis through archival data, photographs, and literature such as books and journals related to the discussion of kebaya and social class in the Dutch East Indies. The results show that kebaya not only functions as a traditional dress, but also as a symbol that reflects and influences a woman's social class. During the colonialism era, kebaya was worn by aristocrats and commoners, including women of Chinese and Dutch descent. This successfully demonstrated their adaptation to the local culture. The variety of designs, patterns, colours and materials of the kebaya itself reflected the social status that maintained the social structure in colonial society. Various types of kebaya were also created in the colonial era such as Kebaya Kartini, Kebaya Encim, European Kebaya, and others. Through the habitus perspective, kebaya can be understood as part of a social habit that is influenced by social structure and history. This research provides a new perspective by applying Pierre Bourdieu's habitus theory, which helps explain how kebaya is not only a garment but also a symbol of status and identity that is acquired and maintained through social practices. The significance of this research is that it enriches the understanding of how kebaya played a role in the social and cultural dynamics of the colonial period in Indonesia. In conclusion, kebaya was an important tool in the formation and reproduction of social class structures in colonial Java, in accordance with Pierre Bourdieu's habitus theory that links cultural practices with social status positions.